The effect of arbuscular mychorizal fungi (AMF) and root plant growth regulator (rPGR) in increasing number of tea (Camellia sinensis (L.) O. Kuntze) planting material - Cucu Suherman; Wieny H Rizky; Intan Ratna Dewi (Jurnal Penelitian Teh dan Kina, 2015)
Among problems encountered in the availability of quality seedlings in nurseries is a low percentage of seedlings ready to plant. The seedling will remain stunted if no treatment is provided. Therefore, there must be some treat-ments carry in the nursery, as increase seedling ready to plant. One of the problems causing lack of good seedling growth is less than optimal growth and the role of the root, thus, the increase in the growth of the tea plant seeds can be cultivated among others through im-proved root system. The objective of this re-search was to determine the effect arbuscular mycorrhizal fungi (AMF) and plant growth regulator (PGR) against the percentage of root seedlings were ready to plant. Root growth can be accelerated by the application of PGR roots, ability to function and role of the roots can be improved by application of biological fertilizers such as AMF. The experimental design used was a randomized block design combined con-centration of PGR roots consisting of Z0: 0 mg/mL; Z1: 25 mg/mL; Z2: 50 mg/mL; Z3: 75 mg/mL with a dose of FMA consisting of: F0: 0 g FMA/plant; F1: 5,0 g FMA/plant; F2: 7,5 g FMA/plant and F3: 10,0 g FMA/plant. The experiment was conducted at the Gambung Experimental Station at the Research Institute for Tea and Cinchona, Bandung, West Java, at a height of Â± 1.350 m above sea level with the type of Andisols. Rainfall including B-type according to the classification of Schmidt and Fergusson (1951). The experiments resulted in the conclusion FMA 7,5 g dose combination treatment plants PGR-1 with a concentration of 25 mg/mL root, generating growth in both the percentage of root infection, seedling height, the number of leaves, and the amount of leaf chlorophyll and the percentage of tea planting material. The treatment resulted in a 35% increase in plant height, a number of leaves nearly 68% and the amount of chlorophyll is 83% higher compared to treatment without the FMA and without PGR. The percentage of 12 months old planting material with treatment reached 78,11% higher than the treatment without AMF and PGR which reached 49,28%.